If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24(x + 34) = 1200 Reorder the terms: 24(34 + x) = 1200 (34 * 24 + x * 24) = 1200 (816 + 24x) = 1200 Solving 816 + 24x = 1200 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-816' to each side of the equation. 816 + -816 + 24x = 1200 + -816 Combine like terms: 816 + -816 = 0 0 + 24x = 1200 + -816 24x = 1200 + -816 Combine like terms: 1200 + -816 = 384 24x = 384 Divide each side by '24'. x = 16 Simplifying x = 16
| 5-2x=-6x+8+4x-3 | | 0=4x^3-33x^2-76x-48 | | -7(5)(-1)(-1)= | | 870-30m=1200 | | 2x^2-18x-54=0 | | 5x-(7-1x)=36+(-13) | | 2+6x+6=5x+7+2x | | 10(x+2)-8x=19 | | 5x-(7-x)=36+(-13) | | 3=2*7x | | 10y+19.95=139.95 | | 2h-6/4=0.5 | | X^3+3x^2-45x-175=0 | | 2y-3=2+4 | | 4x-3=-2x+3 | | 2h-6/4=.5 | | 3a-2a+7+6a=-28 | | 9-4(2t-1)=45 | | ln(60)=x | | 5-2x=-6+8+4x-3 | | 6x+12+3x+6=58.3 | | rtd=rt | | 11-(-6)= | | (4x-7y)-(x-3y)= | | 6x^2+66x+60=0 | | 25+4x^2-4x=3x^2-6x | | -32x^7-8x^6= | | 12x=x-2(16) | | x+.20x=34.80 | | -25+4(2x+5)=-16 | | 2x+3-7x+2=10 | | 3(n+7)=-6 |